Closed Beta Testing on e-Label Batik Application to Know the Best Environment for Optimal Application Performance - Paminto Agung Christianto (Politeknik Negeri Semarang, 2019)
—The Batik of Pekalongan is a heritage that continues to be maintained and until now it is still used as a source of livelihood for the majority of the people in Pekalongan city, so the city of Pekalongan is known as the city of batik. However, the existence of batik is facing a serious threat, caused by the abundance of textile products with batik motifs (batik printing) on the market, but not matched by increased public knowledge of batik. Various efforts, both in Pekalongan city government through the labeling of batik, and ASEPHI in Pekalongan city through the implementation of original batik hologram, has been done to maintain the sustainability of batik. But this has not yet provided optimal results, because it is still found that the fraudulent batik seller who put the original batik label/hologram on batik printing, thus harming the society, harming batik craftsmen/producers and tarnish the batik image of Pekalongan city. This happened because the batik label or the original batik hologram had not been connected to a computer-based information system, so that they cannot monitor and validate the attachment of original batik labels/holograms. For this reason, researchers developed a e-label batik application that was able to be used by the community to scan batik labels that produced by the e-label batik application, so that can know information the authenticity of the batik. The application is also equipped with facilities that provide convenience to monitor, validate, get feedback from the community and become a learning media for the community towards batik. The development of e-label batik applications has gone through the stages of alpha testing and continued with closed beta testing to find out the ideal environment, So that the performance of the batik elabel application is optimal, and can be used properly by the community.